Early childhood education, birth-8 : the world of children, families, and educators - Driscoll, Amy.; Nagel, Nancy G. (Boston : Allyn and Bacon, 1999)
Building a community of early childhood professionals. The wonder of children: development and dispositions. Theories of development: foundations for practice. Children's play...
Keywords: Education; Child development; Childhood education; Cases studies; Child development -- Case studies; Education -- Education, childhood -- Case studies